State Regulation of Tourist Activity in View of In-Country Travel Development: Theory and Practice - L. I. Donskova; A. L. Barannikov; A. A. Makarov (Вестник Российского экономического университета имени Г. В. Плеханова)
The analysis of issues connected with state regulation of tourism is acute for the development of in-country travel, especially in previous years due to crises in society, economy and politics. The goal of the research is to characterize the relations of tourism with different spheres of life on the basis of the idea of tourism as a social and economic system and to work out indicators of its efficiency (social and economic). In the system of management in order to support the balance in state administrating and market relations indicators of social and economic efficiency were formulated, the authors pay special attention on social effectiveness and ecological stability. Examples of empiric data concerning state measures of supporting tourism today demonstrate the impact of economic and social factors. Results of estimating trends and regularities of in-country travel with regard to Russian conditions should be taken into account in forecasting and planning the field of tourism and in state regulation of tourism in developing policy in travel.